The GALAH Survey: using galactic archaeology to refine our knowledge of TESS target stars. Issue 4 (16th April 2021) - Clark, Jake T; Clerté, Mathieu; Hinkel, Natalie R; Unterborn, Cayman T; Wittenmyer, Robert A; Horner, Jonathan; Wright, Duncan J; Carter, Brad; Morton, Timothy D; Spina, Lorenzo; Asplund, Martin; Buder, Sven; et al.
ABSTRACT: An unprecedented number of exoplanets are being discovered by the Transiting Exoplanet Survey Satellite ( TESS ). Determining the orbital parameters of these exoplanets, and especially their mass and radius, will depend heavily upon the measured physical characteristics of their host stars. We have cross-matched spectroscopic, photometric, and astrometric data from GALAH Data Release 2, the TESS Input Catalog and Gaia Data Release 2, to create a curated, self-consistent catalogue of physical and chemical properties for 47 285 stars. Using these data, we have derived isochrone masses and radii that are precise to within 5 per cent. We have revised the parameters of three confirmed, and twelve candidate, TESS planetary systems. These results cast doubt on whether CTOI-20125677 is indeed a planetary system, since the revised planetary radii are now comparable to stellar sizes. Our GALAH– TESS catalogue contains abundances for up to 23 elements. We have specifically analysed the molar ratios for C/O, Mg/Si, Fe/Si, and Fe/Mg, to assist in determining the composition and structure of planets with Rp < 4R⊕ . From these ratios, 36 per cent fall within 2$σ$ sigma of the Sun/Earth values, suggesting that these stars may host rocky exoplanets with geological compositions similar to planets found within our own Solar system.